Feasibility, acceptability and potential helpfulness of the PROACTIVE intervention in Flanders, Belgium: A survey study. - Shanshan Wang; Johanna de Almeida Mello; Mary S Mittelman; Anja Declercq (PLoS ONE, 2023)
Background/objectives This study aimed to explore the feasibility of a Flemish adaptation of the New York University Caregiver Intervention (i.e., PROACTIVE intervention) modifying the recruitment and intervention content for informal caregivers of people with early cognitive decline, and across different subgroups. A feasibility study is necessary in order to reduce research waste for intervention adaptation and evaluation. Methods Researchers constructed, tested, and sent out a survey consisting of 43 questions on the following topics: awareness of symptoms of early cognitive decline, levels of cognitive performance using the updated Cognitive Performance Scale (CPS2), acceptability, and potential helpfulness of the intervention, and sociodemographic characteristics. Quantitative data were analyzed using descriptive statistics and logistic regression with SAS 9.4©. Qualitative data were analyzed using an inductive content analysis. Results A total of 463 informal caregivers completed the survey (mean age 58.8 ± 11.8, 83.6% female). Among them, 230 respondents who cared for people with cognitive decline indicated they would probably or certainly participate in the study. Identified factors influencing the recruitment were cognition, co-habitation, education, and employment status. Over half of the target caregivers indicated almost all services from the intervention could satisfy their needs. A majority perceived the PROACTIVE intervention would be helpful (69.4%), especially the CPS2 = 3 (76.1%) and CPS2 = 4 (74.1%) subgroups. Conclusion The recruitment of target participants for a subsequent RCT evaluation study is feasible, and identified associated factors should be considered during the recruitment process. The PROACTIVE intervention and core components except 'peer-group participation' were perceived as helpful by most caregivers. The CPS2 = 3-4 subgroups were most accepting of the intervention and were most likely to benefit from the intervention.